Home Court - Stoudemire, Amar'e; Jessell, Tim (New York, N.Y. Scholastic Press, 2012)
Between sports, school, and working for his father, eleven-year-old Amar'e's life is full and he is not yet ready to concentrate on basketball--but when a group of older boys start hogging the local basketball court he knows that he has to do something to help his friends.
650L
101904
Keywords: Stoudemire, Amar'e; Basketball stories; Bullying; Friendship; Autobiographical fiction; Juvenile works - Fiction